1994
DOI: 10.1146/annurev.iy.12.040194.001041
|View full text |Cite
|
Sign up to set email alerts
|

Function and Activation of NF-kappaB in the Immune System

Abstract: NF-kappa B is a ubiquitous transcription factor. Nevertheless, its properties seem to be most extensively exploited in cells of the immune system. Among these properties are NF-kappa B's rapid posttranslational activation in response to many pathogenic signals, its direct participation in cytoplasmic/nuclear signaling, and its potency to activate transcription of a great variety of genes encoding immunologically relevant proteins. In vertebrates, five distinct DNA binding subunits are currently known which mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,823
1
12

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,414 publications
(1,871 citation statements)
references
References 48 publications
35
1,823
1
12
Order By: Relevance
“…1,39 Transcriptional activation of the genes encoding these adhesion molecules and cytokines is tightly regulated by a transcription factor, NFkB. 4,6,[9][10][11]13,40,41 Under normal conditions, NFkB is usually present with IkB in the cytosol as an inactive complex. However, when grafts are exposed to stimuli after transplantation such as ischemia/reperfusion injury, cells may be activated to promote IkB-phosphorylation, which induces NFkB to translocate to the nucleus and to bind to the promoter region of genes of several major inflammatory mediators, such as IL-1, iNOS, and TNF-a, and upregulate their transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,39 Transcriptional activation of the genes encoding these adhesion molecules and cytokines is tightly regulated by a transcription factor, NFkB. 4,6,[9][10][11]13,40,41 Under normal conditions, NFkB is usually present with IkB in the cytosol as an inactive complex. However, when grafts are exposed to stimuli after transplantation such as ischemia/reperfusion injury, cells may be activated to promote IkB-phosphorylation, which induces NFkB to translocate to the nucleus and to bind to the promoter region of genes of several major inflammatory mediators, such as IL-1, iNOS, and TNF-a, and upregulate their transcription.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Nuclear factor kB (NFkB) is one of such transcription factors for genes whose products are critical for inflammation and immunity. 4 It rapidly translocates from the cytoplasm to the nucleus in response to a variety of extracellular signals and plays a pivotal role in the regulation of inflammatory changes by inducing coordinated transactivation of genes of major inflammatory mediators such as IL-1, IL-6, iNOS, and TNF-a [5][6][7][8][9][10][11] and adhesion molecules such as ICAM-1 and VCAM-1. [12][13][14] Cooper et al demonstrated a time-dependent increase in the DNA-binding activity of NFkB, which peaked at 3 days before rejection, in a rat cardiac allograft model.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative bursts generating ROS also provide a defence against infectious agents [136]. At toxic concentrations, ROS are capable of damaging cellular membranes, proteins and DNA leading to eventual mitochondrial destruction and cellular apoptosis [123,127,128].…”
Section: Regulation Of Reactive Oxygen Species Productionmentioning
confidence: 99%
“…In most cell types, NF-kB complexes (the prototype is the heterodimer p50/p65) are found in the cytoplasm as inactive forms, associated with a class of inhibitor proteins called IkBs. The activation of NF-kB may follow a wide variety of extracellular stimuli that lead to the phosphorylation, dissociation and subsequent degradation of IkB, thereby allowing NF-kB to be translocated to the nucleus where it can bind to speci®c cis-acting consensus sequences (kB sites) located in the promoters and enhancers of inducible genes (for reviews see Baeuerle and Henkel, 1994;Grilli et al, 1993;Siebenlist et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…NFkB complexes are involved in the induction of gene encoding hematopoietic growth factors (e.g. IL-2, IL-6, G-CSF and GM-CSF), as well as growth control proteins (p53, c-myc, ras) (for review see Baeuerle and Henkel, 1994). Increased NF-kB activity occurs in response to a variety of growth stimuli, and this has been implicated in the proliferation of murine ®broblasts transformed by the p40Tax protein of human T-cell leukemia virus 1 (Kitajima et al, 1992).…”
Section: Introductionmentioning
confidence: 99%